Proporção dos Tratamentos Endodônticos Concluídos no SUS nos Municípios Brasileiros - Santos, Albina de Fatima Fanni (2022)
The preservation of teeth in the oral cavity is of great importance for the continuity of oral functions, helping to maintain the patient's health. The pathologies that cause acute inflammatory processes, periapical or pulp, are some of the reasons that most lead patients to seek dental care in the SUS. The implementation of Dental Specialty Centers, through the Brasil Sorridente Program, enabled a greater offer of this specialized service. Taking into account endodontics as a specialty that helps in the maintenance of dental elements in the oral cavity, this study had the general objective to analyze the conclusion of endodontic treatments in the SUS in Brazilian municipalities, in the year 2018. The type of study was ecological, being carried out based on secondary data in the public domain and at the municipal aggregation level. Data were taken from the National Registry of Health Establishments, from the SUS. Outpatient Information System, IBGE, and from the latest evaluation of the Program for Improving Access and Quality of Dental Specialty Centers. Analysis of the collected data were organized in a database to be analyzed and compared with the completeness of endodontic treatments, based on the available literature. Variables from the Access and Quality Improvement Program for Dental Specialty Centers and sociodemographic variables were used to better understand these results. The results of the study showed that the highest performance regarding specialized endodontic services in the SUS was associated with municipalities with smaller population sizes, with lower HDI-M, with lower dental plan coverage and with better performance in the 2nd cycle of the PMAQ CEO. In addition to investments in the structure and work process of the CEO, the improvement of public endodontic dental services in Brazil involves positive impacts on the country's oral health after the implementation of the PNSB and the principle of equity in specialized endodontic care in the SUS, given its positive impact especially in small municipalities and with less social development.